Juridical Analysis of Illegal Information Access: Case Study on Sales of Data Patients Covid-19 - Kessa Hendriyanto (SOEPRA, 2021)
Abtract: Increasingly sophisticated technology and information systems provide their own risks, namely with the presence of cyber of cyberspace (cybercrime). The fundamental foundation of the emergence of crime, whatever its type and kind, is still largely based on the profit and personal gain motive.Information related to COVID-19 patients is sensitive information in the community lately. Some parties refuse to disseminate COVID-19 patient data due to privacy and security reasons, while those who support it reason that it needs to be done in the context of contact tracing in order to prevent the dissemination of the COVID-19 pandemic.With the case of selling COVID-19 patient data through an online forum, demanding a study in the aspect of the impact of COVID-19 patient data distribution. In addition, the study was also carried out related to arrangements in the field of health, the field of public information disclosure, and the field of information and electronic transactions to find out what was the basis of the Government in determining public policy.In this case, the Government implement public policy to disseminate data on COVID-19 patients on a limited basis, namely by not providing detailed information.Keywords: COVID-19 Patient Data, Public Information Disclosure, Privacy, Contact Tracing Abstrak: Semakin canggihnya sistem teknologi dan informasi memberikan risiko tersendiri, yaitu dengan adanya kejahatan siber atau dunia maya (cybercrime). Landasan fundamental timbulnya kejahatan, apapun jenis dan macamnya, sebagian besar masih didasarkan pada motif profit dan personal gain.Informasi terkait dengan pasien COVID-19 merupakan informasi yang sensitif di masyarakat akhir-akhir ini. Beberapa pihak menolak untuk menyebarluaskan data pasien COVID-19 dengan alasan privasi dan keamanan, sedangkan pihak yang mendukungnya beralasan hal tersebut perlu dilakukan dalam rangka contact tracing demi mencegah penyebarluasan pandemi COVID-19.Dengan adanya kasus penjualan data pasien COVID-19 melalui forum online, menuntut akan adanya kajian terkait dampak tersebarnya data paseien COVID-19. Selain itu, kajian juga dilakukan terkait dengan pengaturan di bidang kesehatan, bidang keterbukaan informasi publik, dan bidang informasi dan transaksi elektronik untuk mengetahui apa yang dijadikan landasan Pemerintah dalam menentukan kebijakan publik.Dalam hal ini, Pemerintah melaksanakan kebijakan publik untuk melakukan penyebarluasan data pasien COVID-19 secara terbatas, yaitu dengan tidak memberikan informasi detail.Kata Kunci: Data Pasien COVID-19, Keterbukaan Informasi Publik, Privasi, Contact Tracing